2016
DOI: 10.12693/aphyspola.130.1033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Energy Milling Time on the Ti-50Ta Biomedical Alloy Structure

Abstract: Nickel-free titanium alloys are a promising research direction in the field of biomedical materials. Current literature reports indicate that there is a possibility of using the Ti-Ta alloys in medicine since these alloys have had satisfactory results as far as biocompatibility, resistance to corrosion and mechanical properties are concerned, which is an important aspect while considering the use of this alloy for long-lasting bone implants. This article presents the results of a high-energy milling process wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The literature has indicated that as little as 25% wt. Ta can cause the appearance of the β-phase and, with increasing tantalum content, the β-phase proportion increases [ 13 , 27 , 28 , 29 , 30 ]. We also detected a non-stoichiometric phase of Zr0.11Ti0.89, likely located in the transition zones.…”
Section: Resultsmentioning
confidence: 99%
“…The literature has indicated that as little as 25% wt. Ta can cause the appearance of the β-phase and, with increasing tantalum content, the β-phase proportion increases [ 13 , 27 , 28 , 29 , 30 ]. We also detected a non-stoichiometric phase of Zr0.11Ti0.89, likely located in the transition zones.…”
Section: Resultsmentioning
confidence: 99%
“…The fracture process occurs when the larger particles disintegrate into smaller pieces due to overloading as a result of continuous collisions [7,8]. Depending on the ductility of the used material being milled, fracturing or cold welding can dominate and result in the formation of a lot of small particles, or when there is complete cold welding with the balls and the walls of the milling bowls the process s efficiency and material recovery are negatively affected [3,[9][10][11][12]. Therefore, maintaining a suitable relationship regarding the cold welding and fracturing phenomena ensures a stable particle size.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that, in the case of a planetary ball mill, the mechanical alloying of the material results mainly from the strong interactions of the material with the balls during the rotation of the bowls [13,14]. In addition, MA is a process that allows materials of different structure types to result in amorphous [15], nanocrystalline [12,16,17] and porous materials [13,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the scientific literature, there are evidences of successful preparations of titanium-based materials with this production method. [8][9][10] This production method has a number of significant advantages. It allows creating alloys of materials with large differences between their melting temperatures or densities.…”
Section: Introductionmentioning
confidence: 99%